A prospective pilot study of detection of sentinel lymph nodes in gynaecological cancers using a novel near infrared fluorescence imaging system - Laios, Alexandros; Volpi, Davide; Tullis, Iain D. C.; Woodward, Martha; Kennedy, Stephen; Pathiraja, Pubudu N. J.; Haldar, Krishnayan; Vojnovic, Borivoj; Ahmed, Ahmed A. (BMC research notes, 2015)
Background Sentinel Lymph Node (SLN) sampling may significantly reduce surgical morbidity by avoiding needless radical lymphadenectomy. In gynaecological cancers, the current practice in the UK is testing the accuracy of SLN detection using radioactive isotopes within the context of clinical trials. However, radioactive tracers pose significant logistic problems. We, therefore, conducted a pilot, observational study to assess the feasibility of a novel optical imaging device for SLN detection in gynaecological cancers using near infrared (NIR) fluorescence. Methods A novel, custom-made, optical imaging system was developed to enable detection of multiple fluorescence dyes and allow simultaneous bright-field imaging during open surgery and laparoscopic procedures. We then evaluated the performance of the system in a prospective study of 49 women with early stage vulval, cervical and endometrial cancer who were scheduled to undergo complete lymphadenectomy. Clinically approved fluorescent contrast agents indocyanine green (ICG) and methylene blue (MB) were used. The main outcomes of the study included SLN mapping detection rates, false negative rates using the NIR fluorescence technique and safety of the procedures. We also examined the association between injection sites and differential lymphatic drainage in women with endometrial cancer by fluorescence imaging of ICG and MB. Results A total of 64 SLNs were detected during both open surgery and laparoscopy. Following dose optimisation and the learning phase, SLN detection rate approached 100 % for all cancer types with no false negatives detected. Fluorescence from ICG and MB detected para-aortic SLNs in women with endometrial cancer following uterine injection. Percutaneous SLN detection was also achieved in most women with vulval cancer. No adverse reactions associated with the use of either dyes were observed. Conclusions This study demonstrated the successful clinical application of a novel NIR fluorescence imaging system for SLN detection across different gynaecological cancers. We showcased the first in human imaging, during the same procedure, of two fluorescence dyes in women with endometrial cancer.